2019
DOI: 10.1093/brain/awz105
|View full text |Cite
|
Sign up to set email alerts
|

Loss of STEP61 couples disinhibition to N-methyl-d-aspartate receptor potentiation in rodent and human spinal pain processing

Abstract: Dysregulated excitability within the spinal dorsal horn is a critical mediator of chronic pain. Dedek et al. report that downregulation of tyrosine phosphatase STEP 61 links disinhibition to NMDAR potentiation in human and rodent spinal pain processing, and develop an ex vivo human preclinical model to help bridge the translational divide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 48 publications
6
92
2
Order By: Relevance
“…The superficial layers of the spinal cord dorsal horn, laminae I and II, are a hub for processing pain-related sensory inputs [1]. Disruption in the balance of excitability within the superficial dorsal horn can drive chronic pain [2], and yet the specific molecular determinants that mediate synaptic signaling across dorsal horn neuron subpopulations remain poorly understood. The N-methyl-D-aspartate receptor (NMDAR) subtype of ionotropic glutamate receptors are critical mediators of synaptic transmission and plasticity throughout the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…The superficial layers of the spinal cord dorsal horn, laminae I and II, are a hub for processing pain-related sensory inputs [1]. Disruption in the balance of excitability within the superficial dorsal horn can drive chronic pain [2], and yet the specific molecular determinants that mediate synaptic signaling across dorsal horn neuron subpopulations remain poorly understood. The N-methyl-D-aspartate receptor (NMDAR) subtype of ionotropic glutamate receptors are critical mediators of synaptic transmission and plasticity throughout the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Together, the previous studies demonstrate causality of KCC2 downregulation in pathologic pain. Interestingly, recent results suggested that this mechanism also might apply to human spinal pathophysiology in pathologic pain (Dedek et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic pathologic pain, KCC2 expression is attenuated in the primary sensory gate in spinal cord dorsal horn neurons. This key pathophysiological mechanism contributes to an excitation/inhibition imbalance by corrupting inhibitory neurotransmission and causing inhibitory circuit malfunction (Braz et al, 2017;Dedek et al, 2019;Doyon et al, 2013;Ferrini et al, 2013;Kahle et al, 2014a;Li et al, 2016;Mapplebeck et al, 2019;Price et al, 2005). Notably, there is no 'back-up' protein that can rescue the KCC2 expression deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation-induced hyperalgesia leads to decrease in STEP61 activity (by both phosphorylation at serine 221 residue and cleavage) with concurrent increases in phosphorylated GluN2B in the spinal cord [82,83]. In 2019, we showed that STEP61 is significantly reduced at the superficial dorsal horn in a persistent inflammatory pain model and an ex vivo BDNF model of pathological pain processing [84].…”
Section: Step61 -The Linker Between Disinhibition and Increased Excitmentioning
confidence: 69%
“…The images were taken at 63x for high magnification. Quantification and changes in KCC2 intensity was detected using MATLAB routines as previously described [84]. In brief, CGRP was used as a marker of the superficial dorsal horn and only the neurons the CGRP expressing region was quantified.…”
Section: Quantification Of Kcc2 Expressionmentioning
confidence: 99%